Spatial distribution of investment incentives and the impact of new incentive system for less developed regions in Turkey - Onur Sungur (Review of Economic Perspectives, 2019)
Regional policy has been on the agenda of Turkey since the First Five-Year Development Plan (1963−1967), and so far, Turkey has put into practice to overcome regional disparities, one of the most important is regional-sectoral incentives. Thus, the incentive system, which has undergone many changes until today, has been revised and updated in 2012. Although this incentive system has been put into practice for increasing the investment in eastern provinces/regions, development gap between eastern and western regions still stands. The main purpose of this study is to investigate the success of the new incentive system and to determine whether the new investment incentive system is effective in shifting investments from developed regions to backward regions in Turkey. In the study, the regional distribution of investment incentives during 2001−2016 and the effect of new investment incentive system to change the distribution of investments in favor of less developed provinces/regions will be examined. By using investment incentives data, regional distribution of investments will be revealed with the help of map-graph technique. The study found that both the share of incentive certificates and the share of the investment amount have increased during the period of 2001−2016 in the less developed provinces. From this point of view, it is possible to say that the new investment incentive system has a positive impact on increasing the share of incentives in these provinces.
Keywords: R11; R12; R58; 330; Regional Development; Regional Disparities; Investment; Incentives